2012
DOI: 10.1109/tns.2012.2206053
|View full text |Cite
|
Sign up to set email alerts
|

Design Study of the Absorber Detector of a Compton Camera for On-Line Control in Ion Beam Therapy

Abstract: International audienceThe goal of this study is to tune the design of the absorber detector of a Compton camera for prompt γ-ray imaging during ion beam therapy. The response of the Compton camera to a photon point source with a realistic energy spectrum (corresponding to the prompt γ-ray spectrum emitted during the carbon irradiation of a water phantom) is studied by means of Geant4 simulations. Our Compton camera consists of a stack of 2 mm thick silicon strip detectors as a scatter detector and of a scintil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Polf et al showed the feasibility of using a prototype CC to image PG rays emitted during proton beam irradiation. Because a coincidence event (i.e., the PG interacts with both the scatterer and absorber detectors) has a high probability of being detected, numerous studies have evaluated the performance of two‐stage CCs . Similarly, the optimization of the detection efficiency and the spatial resolution of two‐stage CCs has been evaluated .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polf et al showed the feasibility of using a prototype CC to image PG rays emitted during proton beam irradiation. Because a coincidence event (i.e., the PG interacts with both the scatterer and absorber detectors) has a high probability of being detected, numerous studies have evaluated the performance of two‐stage CCs . Similarly, the optimization of the detection efficiency and the spatial resolution of two‐stage CCs has been evaluated .…”
Section: Introductionmentioning
confidence: 99%
“…Because a coincidence event (i.e., the PG interacts with both the scatterer and absorber detectors) has a high probability of being detected, numerous studies have evaluated the performance of two‐stage CCs . Similarly, the optimization of the detection efficiency and the spatial resolution of two‐stage CCs has been evaluated . Hilaire et al showed that using events within an energy window of 0.5–2.5 MeV can improve the performance of a two‐stage CC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to collimated cameras, Compton cameras have also been proposed (Roellinghoff et al, 2011;Richard et al, 2012) in order to increase the counting statistic by eliminating absorbing collimating devices. The Compton camera is an electronically collimate detection system, which generally consists of a stack of scattering detectors followed by an absorbing detector (Roellinghoff et al, 2011).…”
Section: Alternatives To Pet Imaging For Treatment Delivery Verificationmentioning
confidence: 99%
“…Bismuth germanate oxides can be used for gamma radiation [4], but the most striking application is in the medicine area, where BGO crystals are used as absorber detectors of a Compton camera for prompt γ-ray imaging during ion beam therapy [5]. In these applications, a scintillator is a streaked block of bismuth germanate oxide (BGO) providing 8 × 8 pseudo pixels and compared with materials such as LaBr 3 :Ce and LYSO:Ce detectors.…”
Section: Introductionmentioning
confidence: 99%